Ministry of Religion Innovation in Digitalization-Based Hajj Dormitory Services: Si-Mashaji Application - Hendrizal; Aldri Frinaldi (Ilomata International Journal of Social Science, 2023)
The Hajj Dormitory Management Information System application is used as a digital-based service booster that makes it easier for people as service users to book facilities and get information related to Hajj dormitories. This research uses a qualitative descriptive approach with case studies, while the data used comes from secondary data sources from SI-MASHAJI and primary data from the interview process with informants. Data analysis was performed using SWOT analysis. This paper also explains the typology of innovation in the public sector and classifies the SI-MASHAJI application as a newly used public service innovation. The conclusion is that the Ministry of Religious Affairs of the Republic of Indonesia has tried to transform and adapt to the 4.0 era where services in Hajj dormitories are carried out digitally through the SI-MASHAJI Application. Service users in the Hajj dormitory will get all kinds of convenience in the field of services and information services in the Hajj dormitory and SI-MASHAJI is applied to support the value of accountability in the Ministry of Religious Affairs, especially in the Hajj dormitory.